Higienização e saúde na escola: análise de documentos disponíveis antes e durante a pandemia do COVID-19 - Muniz, Bárbara Laís Garcia (Universidade Federal de São Carlos, 2023)
Before the COVID-19 pandemic, the importance of teaching health and hygiene in schools was already recognized and documented, with theoretical content on the relevance of hygiene. However, even with the availability of these materials, many Brazilian schools still suffered from the spread of disease. With the arrival of the pandemic, new documents were prepared, further highlighting the importance of care within the school environment. To investigate the relationship between theory and practice with regard to health and hygiene, a literature review was carried out, focusing on four main documents: "Hygiene and Safety in Schools", "Programa Saúde na Escola (PSE) ", "National Curriculum Parameters (PCN)" and "Guide for the Implementation of Protocols for Returning Face-to-Face Activities in Basic Education Schools". To deepen the research, a practical investigation was carried out in a public basic education school in Sorocaba, state of São Paulo. Practical research led to the conclusion that, despite the existence of documents, schools, professionals and students need practical materials to guide healthy and hygienic practices, in order to avoid the proliferation of pathogens and increase students' understanding of the subject.
Hygiene and health at school: analysis of documents available before and during the COVID-19 pandemic
Keywords: Higiene; Saúde; Covid-19; Diretrizes; Ambiente Escolar; Hygiene; Health; Guidelines; School Environment; CIENCIAS DA SAUDE